Challenges and perspectives in preventing and treating obesity - Pajecki, Denis; Pêgo Fernandes, Paulo Manuel (São Paulo Medical Journal, 2025)
The American Medical Association recognized obesity as a chronic disease in 2013, followed by the World Health Organization. At that time, the global incidence and prevalence of obesity had already been progressively increasing for at least three decades. This scenario has not changed; recent data estimate that 1 billion people worldwide will be obese by 2030. The Brazilian Institute of Geography and Statistics has reported that 25% of the adult Brazilian population lives with the disease, a percentage that has quadrupled in children and adolescents since the 1990s.